Incomplete Stevens–Johnson syndrome secondary to atypical pneumonia. (7th October 2011) - Ramasamy, Anantharaman; Patel, Chiraush; Conlon, Christopher
Abstract : Steven-Johnson syndrome is a common condition characterised by erythematous target lesions on the skin and involvement of the oral mucosa, genitals and conjunctivae. It has been documented as one of the extra-pulmonary manifestations of Mycoplasma pneumoniae infection. Recently, there has been several documentation of an incomplete presentation of this syndrome – without the typical rash but with mucosal, conjunctival and genital involvement. Our case illustrates that the incomplete Steven-Johnson syndrome may present with oral mucosal and conjunctival involvement alone without skin or genital involvement. This important clinical diagnosis should not be missed due to its atypical presentation. Treatment of Steven-Johnson syndrome remains supportive along with treating the underlying infection if recognised.